PERILAKU KONSUMEN MEMBELI PAKET TOUR DI PT.SMEVASINDO HOLIDAY TOUR & TRAVEL PEKANBARU - Darminto, Riki; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research aimed about Consumer Behaviour Buying Tour Package in PT. Smevasindo Holiday Tour & Travel Pekanbaru. This research aims to: (1) to know about Consumer Behaviour Buying A Package Tour in PT. Smevasindo Holiday Tour & Travel Pekanbaru. (2) to know the response of respondents to purchase tour package in PT.Smevasindo Holiday Tour & Travel Pekanbaru.This research was used descriptive quantitatif method to describe the issues. The sample used in this research was 24 people.The results of this research indicate that based on the research results obtained on Consumer Behaviour Buying Tour Package in PT. Smevasindo Holiday Tour & Travel Pekanbaru is agree. This is evidenced by the acquisition of the overall total score of problem recognition, information search, alternative evaluation, product choice, and post purchase evaluation, which is 949 points..Keywords: Consumer Behaviour, PT.Smevasido Holiday Tour & Travel Pekanbaru